Выполните действие: (m-1/2)^2; 2)(а-1/5)^2 3)(х/2-y/3)^2 4)(a/4-b/3)^2 5)(2 1/3 a+ 1...

0 голосов
36 просмотров

Выполните действие: (m-1/2)^2;
2)(а-1/5)^2
3)(х/2-y/3)^2
4)(a/4-b/3)^2
5)(2 1/3 a+ 1 1/2b)^2


Алгебра (56 баллов) | 36 просмотров
Дан 1 ответ
0 голосов
Правильный ответ

1) 
\displaystyle (m- \frac{1}{2})^2=m^2-2* \frac{1}{2}m+( \frac{1}{2})^2=m^2-m+ \frac{1}{4}

2) 
\displaystyle (a- \frac{1}{5})^2=a^2-2* \frac{1}{5}a+( \frac{1}{5})^2=a^2- \frac{2}{5}a+ \frac{1}{25}=a^2-0.4a+ 0.04

3) 
\displaystyle ( \frac{x}{2}- \frac{y}{3})^2=( \frac{x}{2})^2-2* \frac{x}{2}* \frac{y}{3}+( \frac{y}{3})^2= \frac{x^2}{4}- \frac{xy}{3}+ \frac{y^2}{9}

4) 
\displaystyle ( \frac{a}{4}- \frac{b}{3})^2= \frac{a^2}{16}-2* \frac{a}{4}* \frac{b}{3}+ \frac{b^2}{9}= \frac{a^2}{16}- \frac{ab}{6}+ \frac{b^2}{9}

5)
\displaystyle (2 \frac{1}{3}a+1 \frac{1}{2}b)^2=( \frac{7}{3}a+ \frac{3}{2}b)^2= \frac{49}{9} a^2+2* \frac{7}{3}a* \frac{3}{2}b+ \frac{9}{4}b^2=\\= 5 \frac{4}{9}a^2+ 7ab+2 \frac{1}{4}b^2

(72.1k баллов)